LANGUAGE AND CULTURAL IMPERIALISM: INDONESIAN CASE - Pradana Boy ZTF (INTERNATIONAL JOURNAL ON LANGUAGE, RESEARCH AND EDUCATION STUDIES, 2017)
The discourse of language, culture and imperialism are closely intertwined. In this paper I will describe cultural imperialism through language by taking Indonesian case as an example. This essay will develop two main arguments. Firstly, it sets forth that language is a medium through which cultural imperialism could take place, since language is an important and even fundamental aspect of culture. The cultural imperialism through language starts to occur when a certain foreign language is arbitrarily and irresponsibly used in correspondence and combination with local languages within formal and colloquial contexts. Secondly, using Frantz Fannon’s theory as described in his Black Skin White Masks, Indonesian case of use of mixed language of Bahasa and English in any medium is an obvious example of how this language imperialism in contemporary setting arises. Keywords: language, identity, culture, imperialism, Indonesia